PERILAKU BISNIS MUHAMMAD SAW SEBAGAI ENTREPRENEUR DALAM FILSAFAT EKONOMI ISLAM - Mutia Khaira (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
This study discusses descriptively through history and philosophy approach about business behavior Muhammad pbuh. that began after he became goatherders to become enterpreneurs. Muhammad pbuh. suffered setbacks and bounce back from adversity business too. Islamic business behavior that free of riba (interest), gharar (uncertainty) and maysir (gambling) are considered better it because the terms value. Therefore extracting the values of Islamic economic philosophy through business behavior Muhammad pbuh. expected be a solution for business behavior today.